Risk factors for calcification in chronic pancreatitis: a systematic review and meta-analysis - Eperjesi, Orsolya; Németh, Jázmin; Rancz, Anett; Fazekas, Karen Krisztina; Brigitta, Teutsch; Papp, Renáta; Hegyi, Peter; Bunduc, Stefania (Frontiers in Medicine, 2025)
Background/objectivesPancreatic calcifications are the most common structural change in chronic pancreatitis (CP). They can be associated with increased morbidity and healthcare costs. The factors associated with calcifying CP phenotype are not fully understood. Therefore, we aimed to investigate risk factors for calcification in patients with CP.MethodsThe study protocol was registered in PROSPERO(CRD42024591837). On September 18, 2024, we systematically searched three databases (PubMed, EMBASE, and CENTRAL) for studies reporting factors associated with calcifications in CP. Pooled odds ratios (OR) with 95% confidence intervals (CI) were calculated using a random-effects model.ResultsThe systematic search resulted in 10,893 articles, of which 80 eligible studies were identified, covering a total of 31,017 participants. Among risk factors investigated, alcohol consumption (OR = 2.31, CI: 1.80–2.98) and smoking (OR = 2.22, CI: 1.61–3.06) were associated with a twofold increase in odds of calcification when compared to non-smokers and non-drinkers, respectively. The odds of calcification were also 45% higher in alcoholic versus idiopathic CP (OR = 1.45, CI: 1.00–2.11). In contrast, the presence of cystic fibrosis transmembrane conductance regulator (CFTR) mutations did not increase the risk of calcification in CP (OR = 0.43, CI: 0.11–1.66) when compared to CFTR wild-type patients.ConclusionModifiable risk factors, such as alcohol consumption and smoking, were significantly associated with calcifying CP phenotype. It is essential to incorporate smoking cessation and alcohol consumption reduction programs into the standard of care for CP.